Decavanadate contribution to vanadium biomarkers - Aureliano, M. (2016)
The levels of vanadium in urine and blood can be used as biomarkers of exposure, but the mechanism of vanadium toxicity is of major relevance in order to understand how biomarkes can be valuable. Our research group has performed in vivo and in vitro studies using fish and rat models to analysed and compare the toxicity effects induce by vanadium(V) species in the forms of vanadate (V1) and decavanadate (V10). Vanadium toxicological studies often disregarded the formation of decameric vanadate species (V10) known to interact, in vitro, with high-affinity with many proteins such as myosin, actin and sarcoplasmic reticulum calcium pump. Among different experimental in vivo conditions, it was analysed different: (i) mode of administration; (ii) fish species; (iii) metal concentration (1 and 5 mM); (iv) tissues; (v) subcellular fractions ; (vi) exposure time and particularly different metal ionic species, such as V1 and V10. It was observed that‘‘decavanadate’’ promote different effects than other vanadate oligomers in catalase activity, glutathione content, lipid peroxidation, mitochondrial superoxide anion production and vanadium accumulation. Moreover, in in vitro studies using fish and rat liver mitochondria, it was observed that decavanadate impared respiration by depolarization of the mitochondrial membrane, wich altered the redox state of complex III. Putting it all together, it is suggested that decavanadate species are much more effective than monomeric vanadate species in inducing changes in several biomarkers. By changing mitochondrial functioning decavanadate migh provoke ROS formation, but further studies are needed to understand V10 contribution to vanadium biomarkers.